Relationship of Mom's Knowledge About Breast Milk Feeding Patterns With Nutritional Status in Children Aged 6-24 Months at Jambur Pulau, Kec. Perbaungan in 2021 - Rini Febrianti; Sulastry Pakpahan; Afrida Yelni; Selly M Pasaribu; Asrul (International Archives of Medical Sciences and Public Health, 2022)
Efforts to improve the health and nutritional status of infants or children through improving community behavior in feeding are an inseparable part of efforts to improve overall nutrition. Complementary foods are given from 4 months to 24 months of age. This study aims to see if there is a relationship between mother's knowledge about complementary feeding patterns with nutritional status in children aged 6-24 months in Jambur Pulau Village, Perbaungan District in 2021. This research method is an analytic survey study with a cross sectional approach. The population in this study were all mothers of toddlers 6-24 months who came to visit Posyandu in May-July. The sampling technique used was Total Sampling, mothers who had toddlers who came to Posyandu in July amounted to 38 people. The results of statistical analysis using SPSS with Chi-Square test. The results obtained that the majority of mothers' knowledge levels about the provision of complementary feeding were in the less category, namely 10 respondents (26.3%), the nutritional status of the majority of underweight children was 10 respondents (26.3%), based on Chi-square test at 90% confidence level obtained p value = 0.003, meaning there is a relationship. The conclusion of this study is that there is a relationship between mother's knowledge about complementary feeding patterns with nutritional status in children aged 6-24 months in Jambur Pulau Village, Perbaungan District in 2021. Suggestions It is hoped that mothers of toddlers can add information and knowledge about the importance of exclusive breastfeeding and improving the quality of breast milk so that complementary feeding does not need to be given early.